Assessoramento psicopedagógico: o lúdico na educação infantil - Melo, Débora Oliveira Sousa de (2015)
The psycho-pedagogical advice is a work focused on the institutional educational psychology, which from knowledge and tools of its own, is primarily directed to the transformation of schools and other educational settings, for maximum quality education for all, in their common contexts. The advice to schools requires a global vision of the institution, taking into account the current situation and the educational project of each, in order to promote their development and prevent possible school failure. The purpose of this research was to know through the psycho-pedagogical advice how teachers work the playful in early childhood education from the methodology, of qualitative nature, in the form action research, whose school evaluated is located in the Miramar neighborhood – João Pessoa/PB. From the data obtained, it can be concluded that there is a lack of educational psychology counseling in educational institution, lack of recreational education by teachers, sufficient resources and hence methods appropriate for student reality and level of student learning. It is hoped that this research that teachers and education professionals can use this study as guidance to new possibilities for intervention, and appropriate methodologies by theoretical framework, knowledge and understanding of the importance of counseling educational psychologist in educational institutions, child, but also, like, on the type of research chosen goal for any school- level academic and pedagogical intervention.